Pemanfaatan perangkat lunak akuntansi dalam penyusunan laporan keuangan bagi siswa SMK Muhammadiyah 9 Jakarta - Reni Hariyani; Tio Prasetio (Penerbit Goodwood, 2021)
Purpose: This community service aimed to introduce the students of XI class of SMK Muhammadiyah 9 Jakarta Accounting Department to accounting software that has reference standards in the field of financial accounting as well as guidelines regarding tax regulations applied in Indonesia in preparing financial reports to become more manageable, effective, efficient, and accurate. Method: The method was giving lectures in the form of accounting cycle theory and practicum methods, in which participants practice the use of accounting software, namely Zahir Accounting version 5.1, through a briefing from the instructor assisted by the Computer Laboratory Assistant and Secretarial Student Assistant from the Budi Luhur Academy of Secretary. Results: The results showed that the training participants could easily use Zahir Accounting and compile financial reports effectively and accurately. Prior to this, the students did know Zahir Accounting software. Conclusion: The results of this activity impact the teaching and learning process in partner places, namely, by using Zahir Accounting software to replace MYOB Accounting, which is included in the school curriculum. Keywords: Accounting software, Zahir Accounting Version 5.1, Financial statements, Easy, Accurate